TRANSLATION TECHNIQUES OF LOSS AND GAIN IN THE TRANSLATION OF NOVEL IF I STAY - Sari, Syaily Mutiara (CaLLs (Journal of Culture, Arts, Literature, and Linguistics), 2020)
This research has an intention of discovering the forms of loss and gain found in thetranslation of Gayle Forman’s novel entitled If I Stay and identifying the translationtechniques that are used in translating them. This is a qualitative descriptive research. Thedata are in the form of words, phrases, clauses, or sentences of the original and itstranslation version Jika Aku Tetap Di Sini by Poppy D. Chusfani that contained loss andgain. They are collected through reading technique and then analyzed by the translationtechniques. The translation techniques suggested by Molina and Albir (2002) is used to dothe research. The results of the research is 120 forms of loss and gain. There are 43 formsof loss and 77 forms of gain. There are 12 forms of linguistic compression, 31 forms ofreduction, 24 forms of amplification, and 53 gain forms of linguistic amplification.Keywords: Translation techniques, loss and gain